(untitled) (Vietnam Journal of Community Medicine, 2024)
Hemophilia A is a hereditary blood clotting disorder with a prevalence of 1/6000 in males. According to the GLOBOCAN database of the International Agency for Research on Cancer of the World Health Organization, among 36 different types of cancer, nonHodgkin lymphoma ranked 8th in males and 10th in females. However, it is very rare for a patient to have both diseases simultaneously. We want to report a case of T-cell non-Hodgkin lymphoma with bone marrow invasion in a patient with severe Hemophilia A. The patient was an 18-year-old male, diagnosed with Hemophilia A at the age of 4, and was regularly treated with recombinant factor VIII. During their most frequent symptoms, the patient had continuous high fever, with axillary lymphadenopathy. The chest wall ulcer gradually spread after the patient had their axillary lymphadenopathy removed, and popular lesions started appearing on their skin. Hemostasis of the ulcerated lesions was difficult despite the patient receiving factor VIII replacement until stable. Biopsy results with specific immune markers for the ulcerated lesions concluded T-cell non-Hodgkin lymphoma with bone biopsy showed bone marrow invasion. The patient was treated with CHOP chemotherapy but went into septic shock during the leukopenia phase and died.